Evaluation of self-efficacy-based intervention: improving school food handlers’ selected food safety behavior - Yoke, Stephenie Wei Wong; Mahyudin, Nor Ainy; Ho, Jo Ann; Ungku Zainal Abidin, Ungku Fatimah (International Association for Food Protection, 2021)
Food safety training of food handlers is commonly used to reduce the incidence of foodborne disease worldwide. Nevertheless, studies have shown that the provision of knowledge alone may not necessarily result in a positive behavior change. Thus, this study aimed to determine the effect of a multiple-component intervention approach, comprising training and a self-efficacy building program, to improve hand washing and contamination prevention behavior among food handlers at public school canteens in Malaysia. Two groups were compared: treatment (n = 31) and control (n = 30). The treatment group received a 2-h on-site interactive training and a self-efficacy building program that incorporated verbal persuasion, role modeling, and practice time. Both groups were measured using a survey and the direct observation method, before and after a 14-day intervention period. Results show that the intervention package produced a significant increase (P < 0.001) in the behavioral compliance, knowledge, and self-efficacy scores for both behaviors. An increase in the overall frequency of soap use and adherence to the correct hand washing technique for the treatment group was recorded, although there is room for improvement in the post intervention hand washing compliance score. Findings from this study provide valuable information on possible ways to improve food safety behavior among school food handlers.